Rational Expectations, Information Signalling and Dividend Adjustment to Permanent Earning - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1994)
We propose a rational signalling model to investigate the information content of dividends. The model provides a direct test on the relation between unexpected dividend and earnings changes. In identifying the component of unexpected dividend changes, we suggest an expectations framework that accounts for the process of dividend adjustment to firms' permanent earnings. A nonlinear regression method is used to estimate the model and test the rationality and signalling hypotheses. Consistent with Healy and Palepu's (1988) findings, the results show that dividends reflect past, current and future earnings information. [ABSTRACT FROM AUTHOR]